Pharmacological Treatment of Acute Heart Failure: Current Treatment and New Targets. Issue 4 (17th November 2013) - Pöss, J; Link, A; Böhm, M
<x xml:space="preserve">Abstract</x> Acute heart failure (AHF) is defined as the rapid onset of, or changes in, the symptoms and signs of heart failure (HF). It is a life‐threatening situation in which diagnosis and initiation of therapy are crucial. The treatment aims are to stabilize the patient, improve clinical symptoms, and increase long‐term survival rates. Few treatments have been investigated in clinical trials. This review summarizes the principles of pharmacologic treatment, the underlying clinical trials, and new pharmacologic targets. Clinical Pharmacology & Therapeutics (2013); 94 4, 499–508. doi:10.1038/clpt.2013.136